Upaya Meningkatkan Hasil Belajar Siswa Kelas IV Pendidikan Agama Islam dengan Model Problem-Based Learning - Herlina, Netti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of fourth-grade students on the material of Q.S. At-Tin in Islamic Religious Education (PAI) using the Problem-Based Learning (PBL) model. The research was conducted at SDN 20 Sentosa for one semester during the 2024/2025 academic year. PBL was chosen to address the limitations of traditional teaching methods that were less effective in motivating students. The results indicated that PBL significantly enhanced student engagement, understanding of the material, and learning outcomes. Challenges included students' adaptation to the new method and the need for more structured lesson planning. The study concludes that PBL is effective in improving PAI learning outcomes and recommends its application in elementary education.